A role for microRNAs in the Drosophila circadian clock. - Kadener, S.; Menet, J.S.; Sugino, K.; Horwich, M.D.; Weissbein, U.; Nawathean, P.; Vagin, V.V.; Zamore, P.D.; Nelson, S.B.; Rosbash, M. (Genes & Development, 2009)
Little is known about the contribution of translational control to circadian rhythms. To address this issue and in particular translational control by microRNAs (miRNAs), we knocked down the miRNA biogenesis pathway in Drosophila circadian tissues. In combination with an increase in circadian-mediated transcription, this severely affected Drosophila behavioral rhythms, indicating that miRNAs function in circadian timekeeping. To identify miRNA-mRNA pairs important for this regulation, immunoprecipitation of AGO1 followed by microarray analysis identified mRNAs under miRNA-mediated control. They included three core clock mRNAs-clock (clk), vrille (vri), and clockworkorange (cwo). To identify miRNAs involved in circadian timekeeping, we exploited circadian cell-specific inhibition of the miRNA biogenesis pathway followed by tiling array analysis. This approach identified miRNAs expressed in fly head circadian tissue. Behavioral and molecular experiments show that one of these miRNAs, the developmental regulator bantam, has a role in the core circadian pacemaker. S2 cell biochemical experiments indicate that bantam regulates the translation of clk through an association with three target sites located within the clk 3' untranslated region (UTR). Moreover, clk transgenes harboring mutated bantam sites in their 3' UTRs rescue rhythms of clk mutant flies much less well than wild-type CLK transgenes.